The role of developing countries in the global fashion industry sustainability discourse: Ghana in perspective - A narrative review - Akosua Mawuse Amankwah; Edward Appiah; Charles Frimpong; Anthony Kent (Center for Science and Technology, IAIN Surakarta, 2024)
Fashion Industry practices globally are considered to have major negative impacts on both the environment and society. Production and consumption have increasingly moved towards the industry’s model of take-create-dispose. As this phenomenon is observed to take center stage in more industrialized and advanced nations, developing countries including Ghana, also contribute directly or indirectly to the negative impacts. Fashion production in Ghana is predominantly centered on small to medium-scale enterprises, and their mode of operation allows for customized small runs tailored to specific end-customers, thereby providing an avenue for exploring sustainable strategies that may have a positive impact on the environment and society. This paper takes a narrative review approach to how the fashion industry in Ghana impacts sustainability and the opportunities to make positive impacts on sustainability at a global level. It demonstrates how Ghana, as a developing country, imports raw materials for both textile and apparel production from counterparts in developing and developed countries and contributes to negative environmental impacts associated with sourcing countries. However, with the emergence of sustainable strategies, local contemporary fashion designers can embrace culturally friendly sustainable models to enhance their practice toward industry sustainability.